Q. 173.7( 3 Votes )

# Find the followin

Answer :

(3x – 5y) × (x + y)

= x (3x – 5y) + y (3x – 5y)

= 3x2 – 5xy + 3xy – 5y2

= 3x2 – 2xy – 5y2

Putting x = - 1 and y = - 2, we have

[3 (-1) – 5 (-2)] [(1) + (-2)] = 3 (-1)2 – 2 (-1) (-2) – 5 (-2)2

(-3 + 10) (-1 – 2) = 3 – 4 – 20

- 21 = - 21

Therefore,

L.H.S = R.H.S

Hence, verified

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Multiply the follNCERT - Mathematics Exemplar

Simplify

<
NCERT - Mathematics Exemplar

Find the followinRD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Simplify:

RD Sharma - Mathematics

Multiply:

RD Sharma - Mathematics